Analisis Penerapan Model Self Directed Learning Terhadap Kemandirian Dan Hasil Belajar Peserta Didik Kelas V Di SDN 01 Wonorejo Kecamatan Gondangrejo Tahun Pelajaran 2022/2023 - Samini Samini; Anita Trisiana; Jumanto Jumanto (Journal on Education, 2023)
The purposes of this research are: 1) To analyze the learning achievement of the teacher providing material from videos and textbooks through the messages of their parents, which of course students learn in one direction by applying the Self Directed Learning model. 2) To analyze the increase in learning independence of fifth grade students at SDN 01 Wonorejo by applying the Self Directed Learning model. 3) To analyze the increase in learning outcomes of class V students at SDN 01 Wonorejo by applying the Self Directed Learning model. The research method used is descriptive qualitative research. The subjects used were 42 students, 2 parents of students, and the class teacher. In selecting research subjects using purposive sampling technique. The data source for this research was carried out at SDN 01 Wonorejo, Gondangrejo District. Data collection techniques used are observation, interviews, and documentation. The validity of this research data uses a triagulation technique. Analysis techniques using: 1) data collection, 2) data reduction, 3) data presentation, 4) drawing conclusions. The results of this study are: 1) The application of Self Directed Learning carried out by Class V teachers at SDN 01 Wonorejo is that the teacher gives learning problems with healthy material, it is important that the sub-material explains that my blood circulation is healthy by showing students videos based on the Android application Tik-Tok. After that the teacher gives students the opportunity to ask questions and formulate problems. Students become more active and creative in completing each lesson 2) The application of the Self Directed Learning model can increase the learning independence of fifth grade students at SDN 01 Wonorejo, namely being able to have a positive influence on student motivation to be more independent on time doing exercises and be more active in participating in learning compared to learning using the 2013 curriculum method. 3) The application of the Self Directed Learning model can improve the learning outcomes of fifth grade students at SDN 01 Wonorejo by making students brave and confident in expressing opinions and the results of their own assignments.